PENERAPAN METODE GUIDED INQUIRY TEACHING DENGAN MEMANFAATKAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN RESPONS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI IPA 3 SMA NEGERI 2 DENPASAR TAHUN PELAJARAN 2019/2020 - Ni Komang Wirasti (Widyadari : Jurnal Pendidikan, 2020)
This study aims to determine the responses and learning outcomes of class XI IPA 3 SMA Negeri 2 Denpasar after implementing the Guided inquiry teaching method by utilizing mathematics learning media. This type of research is classroom action research (PTK). CAR is designed using several cycles consisting of four stages, namely: planning, implementing, observing and reflecting. The subjects of this study were 36 class XI IPA 3 students of SMA Negeri 2 Denpasar in the 2019/2020 academic year and the object of this research was student learning after being given learning with guided discovery methods and using visual learning media. Student learning outcomes are said to be successful individually if they have obtained a value of ≥ 70.Students are classically said to have succeeded if 85% of the total students in the class have scored ≥ 70.The results of the analysis are obtained (1) There is an effect of the guided inquiry teaching method using the media learning in mathematics can increase student response. (2) The guided inquiry teaching learning method by utilizing learning media can improve mathematics learning outcomes in class XI IPA 3 students of SMA Negeri 2 Denpasar in the 2019/2020 academic year.